IPM-recommended insecticides harm beneficial insects through contaminated honeydew - Calvo-Agudo, Miguel; González-Cabrera, Joel; Sadutto, Daniele; Picó, Yolanda; Urbaneja, Alberto; Dicke, Marcel; Tena, Alejandro (Elsevier, 2020)
The use of some systemic insecticides has been banned in Europe because they are toxic to beneficial insects when these feed on nectar. A recent study shows that systemic insecticides can also kill beneficial insects when they feed on honeydew. Honeydew is the sugar-rich excretion of hemipterans and is the most abundant carbohydrate source for beneficial insects such as pollinators and biological control agents in agroecosystems. Here, we investigated whether the toxicity of contaminated honeydew depends on i) the hemipteran species that excretes the honeydew; ii) the active ingredient, and iii) the beneficial insect that feeds on it. HPLC-MS/MS analyses demonstrated that the systemic insecticides pymetrozine and flonicamid, which are commonly used in Integrated Pest Management programs, were present in honeydew excreted by the mealybug Planococcus citri. However, only pymetrozine was detected in honeydew excreted by the whitefly Aleurothixus floccosus. Toxicological studies demonstrated that honeydew excreted by mealybugs feeding on trees treated either with flonicamid or pymetrozine increased the mortality of the hoverfly Sphaerophoria rueppellii, but did not affect the parasitic wasp Anagyrus vladimiri. Honeydew contaminated with flonicamid was more toxic for the hoverfly than that contaminated with pymetrozine. Collectively, our data demonstrate that systemic insecticides commonly used in IPM programs can contaminate honeydew and kill beneficial insects that feed on it, with their toxicity being dependent on the active ingredient and hemipteran species that excretes the honeydew.